2006
DOI: 10.1016/j.nucengdes.2005.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced seismic criteria for piping

Abstract: In situ, or laboratory, experience have shown that piping systems exhibit a very satisfactory seismic behavior. Seismic motion do not achieve to significantly damage piping systems unless large differential motions of anchorage are imposed. Nevertheless, present design criteria for piping are very severe and lead to require a large number of supports, which overly rigidify the piping systems. CEA, in collaboration with EDF and FRAMATOME, are working on proposals for enhanced design methods, less severe, but st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…All these tests displayed a favourable performance of piping systems which remained below yield limits under design level earthquakes; failure of supports or connections to other linked components occurred prior to the failure of the pipe itself. Other authors confirmed an over-conservativeness of relevant design standards; see, among others, Touboul et al (2006), Paolacci et al (2011Paolacci et al ( , 2013b, Hosseinzadeh et al (2013) and Nakamura (2013). Hence, a need for deep numerical and experimental investigations of piping systems and support structures under realistic seismic loading is evident.…”
Section: Background and Motivationmentioning
confidence: 74%
“…All these tests displayed a favourable performance of piping systems which remained below yield limits under design level earthquakes; failure of supports or connections to other linked components occurred prior to the failure of the pipe itself. Other authors confirmed an over-conservativeness of relevant design standards; see, among others, Touboul et al (2006), Paolacci et al (2011Paolacci et al ( , 2013b, Hosseinzadeh et al (2013) and Nakamura (2013). Hence, a need for deep numerical and experimental investigations of piping systems and support structures under realistic seismic loading is evident.…”
Section: Background and Motivationmentioning
confidence: 74%
“…Studies have shown that the present Standards for piping system design under seismic loads are over conservative and modifications have been proposed to relax this over conservatism [19,20]. For example, [20] has applied the present Codes to calculate the stress limit on piping systems and experimental results showed significant discrepancy from the real behavior.…”
Section: Verification Methodsmentioning
confidence: 99%
“…For example, [20] has applied the present Codes to calculate the stress limit on piping systems and experimental results showed significant discrepancy from the real behavior. This aspect has been treated for example in [21].…”
Section: Verification Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They applied these methods to the seismic qualification analysis of a perforated horizontal tube in a nuclear reactor [18]. Touboul et al [19] studied non-linear behaviour of piping systems under seismic loading and proposed simplified methods to solve seismic induced stresses. Sigrist et al [20] presented seismic analysis of a prototype nuclear reactor with fluid-structure interaction modelling and showed that added mass effects have a significant influence on the dynamic response of the nuclear reactor.…”
Section: Introductionmentioning
confidence: 99%